m6A Methylation in Cardiovascular Diseases: From Mechanisms to Therapeutic Potential - Li, Longbo; Xu, Nannan; Liu, Jia; Chen, Zhenzhen; Liu, Xu; Wang, Junnan (Frontiers in Genetics, 2022)
Cardiovascular disease (CVD) is a leading cause of morbidity and mortality worldwide. Recent studies have shown that n6-methyladenosine (m6A) plays a major role in cardiovascular homeostasis and pathophysiology. These studies have confirmed that m6A methylation affects the pathophysiology of cardiovascular diseases by regulating cellular processes such as differentiation, proliferation, inflammation, autophagy, and apoptosis. Moreover, plenty of research has confirmed that m6A modification can delay the progression of CVD via the post-transcriptional regulation of RNA. However, there are few available summaries of m6A modification regarding CVD. In this review, we highlight advances in CVD-specific research concerning m6A modification, summarize the mechanisms underlying the involvement of m6A modification during the development of CVD, and discuss the potential of m6A modification as a therapeutic target of CVD.